2005
DOI: 10.1128/iai.73.9.6075-6084.2005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the dapA - nlpB Genetic Locus Involved in Regulation of Swarming Motility, Cell Envelope Architecture, Hemolysin Production, and Cell Attachment Ability in Serratia marcescens

Abstract: Swarming migration of Serratia marcescens requires both flagellar motility and cellular differentiation and is a population-density-dependent behavior. While the flhDC and quorum-sensing systems have been characterized as important factors regulating S. marcescens swarming, the underlying molecular mechanisms are currently far from being understood. Serratia swarming is thermoregulated and is characterized by continuous surface migration on rich swarming agar surfaces at 30°C but not at 37°C. To further elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 45 publications
1
29
0
Order By: Relevance
“…After purification, GST protein pull-down assay was performed. Separation of captured proteins by SDS-PAGE highlighted three major bands with predicted molecular masses of 99 kDa (band a), 76 kDa (band b), and 50 kDa (band c) after comparison with the negative controls (GST-nlpB Sm [28] fusion and GST protein only) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After purification, GST protein pull-down assay was performed. Separation of captured proteins by SDS-PAGE highlighted three major bands with predicted molecular masses of 99 kDa (band a), 76 kDa (band b), and 50 kDa (band c) after comparison with the negative controls (GST-nlpB Sm [28] fusion and GST protein only) (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The spent supernatants were then concentrated and analyzed by 12.5% sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The separated proteins were transferred to a polyvinylidene difluoride membrane (Amersham) and incubated in blocking buffer (5% milk, 0.1% Tween 20) for 1 h. Further incubations with anti-His monoclonal antibody or anti-pirin Sm polyclonal antibodies were then performed in blocking buffer for 1 h at room temperature, followed by treatment with horseradish peroxidase-conjugated anti-rabbit second antibody for another 1 h before development and X-ray film exposure (28).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Serratia spp., swarming requires close interactions between the environment and the bacterial cells, as well as among the cells, in order to develop a high degree of complex cell coordination within the swarming colony (2,9,13,26,33,35). Previous studies on the regulation of swarming showed that bacterial flagellar, quorum-sensing, and two-component systems are important for swarming (3,7,33).…”
mentioning
confidence: 99%